Konstruktionsgrammatik, regler og funktionsbaseret struktur i neurokognitiv belysning - Boye, Kasper; Harder, Peter (Ny forskning i grammatik, 2017)
This paper outlines a unified understanding of the grammar-lexicon contrast and its neurocognitive underpinning, which builds on and integrates three recent theories: 1) a functional linguistic theory of the grammar-lexicon contrast; 2) a functional theory of neural structure; 3) a theory of procedural and declarative memory. The proposed model is contrasted with Generative Grammar and in particular with Construction Grammar.